Addressing the labour market emergency : the Scottish Government's response to the report by the Enterprise & Skills Strategic Board sub-group on measures to mitigate the labour market impacts from COVID-19.: the Scottish Government's response to the report by the Enterprise & Skills Strategic Board sub-group on measures to mitigate the labour market impacts from COVID-19. (2020) - Unknown
No abstract available